First Mention of Parvocalanus Scotti (Früchtl, 1923) (Copepoda, Paracalanidae) in the Southwestern Atlantic Ocean (Northern Argentinian Waters) - Ramírez, Fernando (2011)
In this work the occurrence of Parvocalanus scotti is recorded for the first time in southwestern Atlantic waters. A description of the specimen found is provided with emphasis in the more relevant taxonomic characters. The specimen of P. scotti was collected on December 12 th. 2001 at the permanent coastal station EPEA (Estación Permanente de Estudios Ambientales), located at 38º28’S 57º41’W, approximately 27 nautical miles southern Mar del Plata, Argentina. At this station, routine surveys are carried out each month with the purpose of study long-term variations in the plankton community (including bacterioplankton, phytoplankton, zooplankton and ichthyoplankton) in relation with environmental factors (physical and chemical). Zooplankton oblique hauls are performed by means of a Minibongo net (18 cm diameter, 67 and 220 μm meshes) from 45 m depth to the surface. Our specimen was captured by the 67 um mesh size. The main characters observed in the P. scotti specimen coincided with those described by Vervoort (1963) for the species. While our specimen was found in ‘Coastal Waters’, due to its proximity to the isobath of 50 m, the EPEA station may at some times be influenced by advection of ‘Middle Shelf Waters’ of subantarctic origin, and on particular occasions by fresh water from La Plata river. An annual cycle typical of temperate seas characterizes this station with a well established thermocline in summer and a vertically homogeneous regime in winter. The variability in the oceanographic conditions prevailing in this location gives place to the presence of eurythermal and euryhaline zooplanktonic components.